Spokane Meeting Full of Interest - AIME AIME (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
T'HE Columbia Section of the A. 1. M. E. took charge of the Western Mining Convention on Oct. 3, and the meeting was held under their auspices. W. L. Zeigler, chairman of the Section, called the session to order. The first paper on the program, "Lead Refining Practice at Bunker Hill Smelter," was presented in per-son by the author, A. F. Beasley, superintendent of the smelter. He pointed out the differences in the refining practice at Bunker Hill from other American refineries. The Bunker Hill plant was the first to adopt the liquation process for silver skims as developed in Australia. Details were given of operating practice with results. F. F. Colcord questioned the author in regard to the kind of metal best suited for kettles, which was said to be cast iron.